Supplementary description of floral morphology of Vaccinium guangdongense W.P.Fang & Z.H.Pan (Ericaceae) - Tong, Yi-Hua; Zeng, Si-Jin; Ni, Jing-Bo; Xia, Nian-He (Phytotaxa, 2018)
The floral morphology of Vaccinium guangdongense is described and supplemented based on living plants with flowers. According to the supplementary description, V. guangdongense can be differentiated from the closely related V. bracteatum by puberulent inflorescence rachis and pedicels, ovate to elliptic bracts, anthers with spurs 0.3 mm long and tubules ca. 1.5 times as long as thecae. The type information, distribution, ecology, conservation status and color photos are also provided.